Frauenleben in Prag Ethnische Vielfalt und kultureller Wandel seit dem 18. Jhdt. - Iggers, Wilma A. (2000)
The book aims to characterize twelve women who lived in Prague coming from different ethnic backgrounds, Czech Gentiles, German Gentiles, Czech Jews, and German Jews. The earliest is Magdalena Dobromila Rettigová in the late 18th century, the most recent Jiřina Šiklová (2014). Mostly on the hand of their own published but also unpublished writings, I want to deal with their lives, values, and the societies in which they lived.